PENGARUH TINGKAT KESEHATAN BANK DENGAN METODE RISK BASED BANK RATING TERHADAP KINERJA KEUANGAN PADA BANK UMUM SYARIAH DI INDONESIA - Sri Wahyuni Asnaini; Fatrilia Rasyi Radita; Siti Maesaroh (Journal Of Communication Education, 2022)
ABSTRACTThe purpose of this study was to examine how much influence the level of bank soundness based on the Risk Based Bank Rating method on the financial performance of Islamic Commercial Banks in Indonesia. Factors or ratios used in the assessment of Risk Based Bank Rating include Risk Profile (Non Performing Financing/NPF and Financing to Deposit Ratio/FDR), Good Corporate Governance (GCG), Earning (BOPO) and capital (Capital Adequacy Ratio/CAR). The research sample consisted of 8 Islamic commercial banks in Indonesia.The results of the data test state that the f-test shows that all variables have an effect on the financial performance of Islamic Commercial Banks in Indonesia. Meanwhile, through the t-test, the Non-Performing Financing (NPF) variable has an influence on the financial performance of Islamic Commercial Banks in Indonesia, while the Financing to Deposit Ratio (FDR), Good Corporate Governance (GCG), Operating Costs to Operating Income (BOPO), and Capital Adequacy Ratio (CAR) has no effect on the financial performance of Islamic commercial banks in Indonesia.Keywords: Healthy Level, Financial Performance, Islamic Commercial BankABSTRAKPenelitian ini bertujuan untuk menguji berapa besar pengaruh tingkat kesehatan bank berdasarkan metode Risk Based Bank Rating terhadap kinerja keuangan pada Bank Umum Syariah di Indonesia. Faktor atau rasio yang digunakan dalam penilaian Risk Based Bank Rating mencakup Risk Profile (Non Performing Financing/NPF dan Financing to Deposit Ratio/FDR), Good Corporate Governance (GCG), Earning (BOPO) dan permodalan (Capital Adequacy Ratio/CAR). Sampel penelitian terdiri 8 bank umum syariah di Indonesia.Hasil pengujian data menyatakan bahwa melalui uji-f menunjukkan bahwa seluruh variabel berpengaruh terhadap kinerja keuangan Bank Umum Syariah di Indonesia. Sedangkan melalui uji-t variabel Non Performing Financing (NPF) memiliki pengaruh terhadap kinerja keunagan Bank Umum Syariah di Indonesia, sementara Financing to Deposit Ratio (FDR), Good Corporate Governance (GCG), Biaya Operasional terhadap Pendapatan Operasional (BOPO), dan Capital Adequacy Ratio (CAR) tidak memiliki pengaruh terhadap kinerja keuangan bank umum syariah di Indonesia.Kata Kunci: Tingkat Kesehatan, Kinerja Keuangan, Bank Umum Syariah